2019
DOI: 10.3389/fmicb.2019.01896
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into the Microbial Co-occurrence and Diversity of 73 Grapevine (Vitis vinifera) Crown Galls Collected Across the Northern Hemisphere

Abstract: Crown gall (CG) is a globally distributed and economically important disease of grapevine and other important crop plants. The causal agent of CG is Agrobacterium or Allorhizobium strains that harbor a tumor-inducing plasmid (pTi). The microbial community within the CG tumor has not been widely elucidated and it is not known if certain members of this microbial community promote or inhibit CG. This study investigated the microbiotas of grapevine CG tumor tissues fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 88 publications
0
17
0
Order By: Relevance
“…The genetic diversity of A. vitis (Ti) isolated in some countries has previously been reported [22,36,37]. The results from cluster analysis based on repetitive sequence-based (rep)-PCR and inter-simple sequence-repeat (ISSR)-PCR data concurrently showed a potential genomic diversity that separates the Virginia strains from the Japanese strains using a total of 12 strains [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic diversity of A. vitis (Ti) isolated in some countries has previously been reported [22,36,37]. The results from cluster analysis based on repetitive sequence-based (rep)-PCR and inter-simple sequence-repeat (ISSR)-PCR data concurrently showed a potential genomic diversity that separates the Virginia strains from the Japanese strains using a total of 12 strains [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, results from MLSA showed some Virginia strains and Japanese strains formed the same cluster (strain LCCH15 belonging to group A, DCCS15B to group B, ACME15 and HNVR15 to group E) (Figure 1, Table 1). Kuzmanović et al [36] reported that genetic varieties of A. vitis (Ti) of 29 strains isolated in European countries and the USA were analyzed by random amplified polymorphic DNA (RAPD) PCR, and sequence analysis of housekeeping genes of dnaK, gyrB, and recA. RAPD divided them into 17 groups, but a phylogenetic tree based on recA gene divided them into four clades [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed the following software for data processing: Fastp software (for quality control of the original sequencing sequence), FLASH software (for sequence splicing), UPARSE software (97% similarity) (for performing OTU clustering and chimera removal) [29,30], and RDP classifier software (using a 70% threshold to compare the fungus and bacteria database to annotate the species information for each sequence). Then, Mothur software was used to analyze and evaluate the OTU similarity level of 97% (0.97) and Student's t-test was used to calculate the difference in the α diversity index between samples.…”
Section: Data Processingmentioning
confidence: 99%
“…The nutrient-rich environment of crown gall tissue is a sink of amino acids and sugars or organic acids that can also be used as nutrients for the growth of several bacterial groups other than the pathogenic agrobacteria. Hence, gall tissue is a suitable environment to be colonized by epiphytic and endophytic populations of bacterial species ( 3 ).…”
Section: Introductionmentioning
confidence: 99%